O tabuleiro, o esquadro e as tintas : sociabilidade maçônica na década de 1870 - Barbero, Rafael Bedenik (2021)
The present work aims to present and analyze aspects of the Freemasonry presence in the political, social and cultural life of Aracaju reflected in the editorials of the periodical "A Fraternidade", which was the main communication vehicle of the Cotinguiba Lodge, edited between the years 1875 and 1876 in the capital city of Sergipe. The concept of Sociability proposed by the historian Alexandre Mansur Barata will be treated in this work, which will be the key concept to unveil the relations and positions of the Sergipan freemasonry in face of the events of the period, both in Aracaju and in Brazil - for example, the Religious Question of the 1870s, where the Cotinguiba lodge reveals its combative position exposed in the periodical's editorials.